Differences in ball sports athletes speed discrimination skills before and after exercise induced fatigue - Thomson, K.; Watt, A.; Liukkonen, J. (Journal of Sports Science & Medicine, 2009)
Substantial research exists in relation to the effect of fatigue on the cognitive skills of athletes. Very few studies in the sport domain, however, have investigated decision-making time and accuracy in relation to the discrimination of the speed of a moving object following exercise at maximal intensity. The purpose of this study was to examine differences in the pre- and post-fatigue speed discrimination skills of elite ballgames athletes to determine if they prioritize accuracy or speed of decision-making when physically exhausted. The participants in the study were 163 males (M = 21.17, SD = 4.18) Estonian national level soccer (n = 79), basketball (n = 63) and volleyball (n = 21) players. Peak oxygen uptake (VO2max) was assessed during completion of an incremental exercise test on a treadmill. Speed discrimination stimuli were images of red square-shapes on a grey background presented moving along the sagittal axis at four different virtual velocities on a computer (PC) screen. Repeated measures MANOVA revealed a significant main effect for the decision-making time factor. A second MANOVA revealed a significant main effect for the decision-making accuracy factor. The soccer group made a significantly lower number of errors than the basketball group (p = 0.015) in pre- and post-fatigue decision-making accuracy. The results showed that athletes' decision-making time decreased and decision-making errors increased after a maximal aerobic capacity exercise task. A comparison of the pre- and post-fatigue speed discrimination skills of experienced basketball, volleyball and soccer players indicated that the only significant difference was for decision-making accuracy between the soccer and basketball groups. The current findings clearly demonstrated that the athletes made decisions faster at the expense of accuracy when fatigued.